FROM LOCAL AGENDA 21 TO SDG LOCALISATION: A PATHWAY FOR SUSTAINABLE DEVELOPMENT IN MIRI - Khalid, Zanudin; Kiky Kirina, Abdillah; Yusfida Ayu, Abdullah; Bemen Wong, Win Keong; Arnold, Puyok (Malaysian Institute of Planners (MIP), 2026)
Local Agenda 21 (LA21) was introduced in Malaysia in 2000 with four local authorities including Majlis Bandaraya Miri (MBM) selected as pioneers for its implementation. The purpose is to establish partnerships between local authorities and the community inachieving sustainable development. This initiative continues with the Sustainable Development Goals (SDGs). Few studies have examined the contribution of LA21 implementation by local authorities in Malaysia to enhancing their capacity to implement the SDGs in their respective localities. Lack of financial and institutional capacity, along with communities' limited awareness, potentially dampened the transition process between the two agendas. This research addresses the question "To what extent does the implementation of the LA21 contribute to the localisation of the SDGs by MBM?" A case study approach was employed, utilising reports and in-depth interviews with key stakeholders, namely public officers, councillors, and academicians. Findings show that MBM's LA21 initiatives, such as solid waste reduction and pollution control, have laid the foundation for localising the SDGs. However, challenges such as financial constraints and a lack of political support hindered the full realisation of these agendas. The research concludes that while LA21 provides a platform for community participation, stronger integration of community involvement and institutional support is necessary to fully localise the SDGs in Miri.